The design and evaluation of a novel vehicle navigation system - Nwakacha, Valentine (2014)
Vehicle Satellite Navigation Systems are commonplace but from a safety point of view, can be problematic. They are situated on small screens and often placed at an angle which is not in the driver’s field of view. This promotes glances away from the road and reduces situational awareness for events which occur. Audio commands and visual maps which are used to instruct drivers typically require translation to situationally meaningful actions before execution in the real world. This increases the driver’s workload and risk of distraction.